ANALISIS DAN DESAIN SISTEM INFORMASI BIAYA PEMASARAN MARKETING PADA PT. YGI AREA SUMATERA - Muryono, Tupan Tri (Infotech: Journal of Technology Information, 2019)
Technology that combines computer technology and telecommunications technology has changed the way of life of individuals and organizations in carrying out business activities or carrying out daily activities. The ability of communication between one organization and other organizations in different places (separated at great distances) is one of the characteristics of the coming era of globalization. The problems that exist in PT. YGI is the absence of a system that can provide marketing information to consumers. This research was conducted to gather information about marketing marketing costs, promotions, rebates, general costs and costs of branch operating funds to make decisions that are more effective, efficient, and easier for management . The author uses the method of collecting data through observation and interviews and based on theories derived from several books or journals related to the method of system design using object-oriented design methods. The results of the design and development of marketing information system marketing analysis design at PT. YGI Area Sumatra can provide solutions to problems faced in the product sales process as well as product marketing solutions for companies so that ordering products from customers increases and relationships increase. With the design of marketing information systems marketing costs can develop and publish products properly and can be seen by consumers as clearly as possible.